Investigating the relationship between conscientiousness, neuroticism and the quiet quitting phenomenon in South Africa: conceptualising quiet quitting as psychological turnover behaviour - Keyter, Jens (Stellenbosch : Stellenbosch University, 2026)
Thesis (MCom)--Stellenbosch University, 2026.